Factors affecting food aid: evaluating new fortified-blended foods and the clinical impact of tannin and phytic acid consumption on iron bioavailability - Delimont, Nicole Marie (Kansas State University, 2017)
Iron, vitamin A, and protein inadequacies are common in food-aid receiving countries, and maximizing nutrient intake and bioavailability are essential treatments. Fortified-blended foods (FBFs), are food-aid micronutrient-fortified legume-grain porridges distributed worldwide. FBFs have not consistently, effectively treated undernutrition, and it has been suggested that formulation and processing changes could improve their nutritional quality. Sorghum is a well suited FBF commodity, but high concentrations of ‘antinutritional’ tannin and phytic acid have limited its adoption. Iron bioavailability adaptation may be possible after long-term antinutritional factor consumption, but adaptive mechanisms are not well understood. In rats, salivary proline-rich proteins (PRPs) have been found to chelate tannins to improve iron bioavailability, this could be true for people as well. Several research design methods were employed to summarize FBF quality outcomes and the effect of tannin and phytic acid consumption on iron bioavailability. Extruded sorghum and corn FBFs were developed; protein quality, iron, and vitamin A outcomes were compared with a non-extruded corn-soy blend (CSB+) in rats. A narrative literature review and meta-analysis were conducted to determine tannin’s antinutritional effects on iron bioavailability, and the potential for adaptation through salivary PRPs. Two clinical trials examined the effect of long-term tannin or phytic acid consumption on iron bioavailability, salivary protein production, and correlations between PRPs and iron bioavailability. There were no differences between iron (hepatic iron 207-300 µmol/g *100), vitamin A (hepatic retinol 423-585.5 ng/mg), or protein quality (caloric efficiency: 101.3-113.3 g/kcal*100) between extruded FBFs regardless of commodity in rats. Compared to extruded FBFs, CSB+ caloric efficiency (49.0 ± 2.2 g/kcal*100) and growth (96.3 ± 3.4g vs. 208.6-236.6) were significantly reduced. A literature review suggested that there were differences in acute meal and long-term iron bioavailability with tannin consumption; tannic acid inhibited iron availability, while food-tannins did not. Meta-analysis suggested that tannin-PRP binding could protect iron bioavailability, that long-term tannin consumption did not significantly affect hepatic iron or non-heme iron absorption respectively in rats (d = -0.64-1.84; -2.7-0.13), and that PRP expression in rats during tannin consumption was correlated with improved iron bioavailability. There were no reductions in iron bioavailability or status based on long-term tannin (ps > 0.126) or phytic acid (ps > 0.08) consumption clinically, but basic PRP and cystatin subtypes were significantly correlated with improved iron bioavailability during tannin (ps < 0.03) and phytic acid (ps < 0.02) consumption. In vitro, it phytic acid-PRP binding did not occur, but phytic acid did specifically bind with cystatin SN, a non-enzymatic salivary protein. In conclusion, FBF formulation changes may improve protein quality, and provide needed macronutrients to food-aid receiving areas. Despite this, this research did not suggest that antinutritional factors affected iron bioavailability. In support of this finding, literature, and clinical studies presented here suggest that salivary proteins, including PRPs and cystatin, may serve as adaptive protective mechanisms against phytic acid and tannin consumption, and that further research may be warranted before further recommendations for their removal from food-aid are made.
Keywords: Iron; Antinutritional factors; Tannins; Phytates; Vitamin A; Protein quality